Features and Prospects of Clusterization of Rural Tourism in Ukraine - Околович, Ірина (Київський національний університет імені Тараса Шевченка, 2022)
The essence and features of clustering in rural tourism are considered. An initial analysis of aspects of the creation and functioning of rural tourism clusters in Ukraine (current state, areas of activity, problems and prospects for their further development) was carried out using the methodology of research semi-structured interviews and qualitative content analysis. The characteristics of the researched rural tourism clusters according to the criteria of geographical location, smart specialization, scale of activity, history of creation, features of the tourist product and target audience are given. Trends in the number and composition of participants and features of the institutional design of clusters of rural tourism in Ukraine are analyzed. Groups of clusters of rural tourism have been identified according to the criterion of their own smart specialization. The main purpose of the creation and functioning of rural tourism clusters in the context of their participants and the region of activity has been revealed. The main areas of activity of clusters of rural tourism in Ukraine are determined: organizational, educational, advertising and marketing, communication, creation of a joint tourist product, development of the community and its tourist potential, and direction of cooperation. The possibilities and features of cooperation of rural tourism clusters with state authorities and local self-government bodies, with scientific and educational institutions, with public associations and with other subjects at the local, regional and national levels are revealed. The main problems faced by the clusters during their activities are identified - external, which characterize the general state of tourism development in the region, and internal, which relate directly to the activity of the cluster. The impact of seasonality on the organization of rural tourism cluster activities has been studied. The peculiarities of planning and prospects for the future development of rural tourism clusters and the level of study and use of other available domestic and foreign experience during the organization of their activities are analyzed. The main groups of benefits that cluster participants receive from joint activities are disclosed - social, marketing, access to knowledge and information, financial, access to resources, and benefits related to the tourist product. Factors determining the success of rural tourism clusters are summarized.

Розглянуто сутність та особливості кластеризації в сільському туризмі. Здійснено первинний аналіз аспектів створення та функціонування кластерів сільського туризму в Україні (сучасного стану, напрямів діяльності, проблем та перспектив їх подальшого розвитку) із застосуванням методології дослідницького напівструктурованого інтерв’ю та якісного контент-аналізу. Наведено характеристики досліджуваних кластерів сільського туризму за критеріями географічного розташування, смартспеціалізації, масштабу діяльності, історії створення, особливостей туристичного продукту та цільової аудиторії. Проаналізовано тенденції щодо кількості та складу учасників та особливостей інституційного оформлення кластерів сільського туризму в Україні. Виділено групи кластерів сільського туризму за критерієм визначення ними власної смартспеціалізації. Виявлено основну мету створення та функціонування кластерів сільського туризму в контексті їх учасників та регіону діяльності. Визначено основні напрями діяльності кластерів сільського туризму в Україні: організаційний, навчальний, рекламно-маркетинговий, комунікаційний, створення спільного туристичного продукту, розвиток громади та її туристичного потенціалу та напрям співпраці. Розкрито можливості та особливості співпраці кластерів сільського туризму з органами державної влади та місцевого самоврядування, із закладами науки та освіти, з громадськими об’єднаннями та з іншими суб’єктами на локальному, регіональному та національному рівнях. Визначено основні проблеми, з якими зіштовхуються кластери під час своєї діяльності - зовнішні, які характеризують загальний стан розвитку туризму в регіоні, та внутрішні, що стосуються безпосередньо діяльності кластера. Досліджено вплив сезонності на організацію діяльності кластерів сільського туризму. Проаналізовано особливості планування та перспективи майбутнього розвитку кластерів сільського туризму та рівень вивчення і використання іншого наявного вітчизняного та іноземного досвіду під час організації їхньої діяльності. Розкрито основні групи вигод, які отримують учасники кластерів від спільної діяльності – соціальні, маркетингові, доступ до знань та інформації, фінансові, доступ до ресурсів та вигоди щодо туристичного продукту. Узагальнено чинники, які зумовлюють успішність кластерів сільського туризму.
Особливості та перспективи кластеризації сільського туризму в Україні
Keywords: туризм; сільський туризм; кластер; кластеризація; кластер сільського туризму; tourism; rural tourism; cluster; clustering; rural tourism cluster